A mixed algorithm for investigation the effects of the preparation processes during the catalyst synthesis with sol-gel method and coating - Bashan, Veysi; Ust, Yasin; Balkanli, Esra; Eren Figen, H. (SPRINGER, 2020)
Catalytic materials are available in several forms and their preparation includes various protocols with many possible preparation schemes. Also, the preparation of any catalyst includes several complex processing sequences, many of which are not fully well known. Therefore, minor changes in preparative details can cause noticeable changes in the properties of the final catalyst. Our aim in this study is to provide the causes and effects relations of the preparation processes by using a fuzzy decision-making trial and evaluation laboratory (DEMATEL) method. The DEMATEL method is used to identify and analyze the problems encountered while preparing the catalyst according to the effect relationship diagram. In addition, fuzzy sets go through uncertainty in decision making and comments from DEMATEL experts. When the results are analyzed it can be seen that homogeneous coating and determining proper calcination temperature is crucial in terms of causes. Besides, it has been found that it is very important to choose correct molar densities, and make the physical properties of the material to be coated suitable in accordance with humidity and temperature. Findings from the study will contribute to proper catalyst preparation and coating. [GRAPHICS] .
Keywords: Algorithm; Catalyst preparation; Fuzzy DEMATEL; Catalyst synthesis; Sol-gel process; CRITICAL OPERATIONAL FAULTS; DECISION-MAKING TRIAL; DEMATEL APPROACH; FUZZY; UNCERTAINTIES; MANAGEMENT; SELECTION; INDUSTRY; STORAGE; SYSTEM; Materials Science